A Venous Island Flap for Thumb Reconstruction* - Shrikant P. Lagvankar (Indian Journal of Plastic Surgery)
A successful transfer of a venous island flap from the dorsum of the proximal phalanx of the index finger to the defect on the proximal phalanx of the thumb is reported.